2004
DOI: 10.1080/00016480410017134
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal reflux in children with chronic otitis media with effusion

Abstract: These findings indicate that pharyngeal reflux may play an important role in the etiology of COM with effusion. If patients have typical symptoms of GER, such as pyrosis, regurgitation, dysphagia and emesis, the presence of GER should be considered. The presence of silent GER and pharyngeal reflux should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 11 publications
0
38
0
1
Order By: Relevance
“…Recent studies have shown that the exposure of the upper aerodigestive tract to gastric secretion results in numerous pathologic conditions. Chronic sinusitis, chronic cough, subglottic stenosis, recurrent croup, laryngomalacia, reflex apnea, asthma, recurrent otitis media [4] and also chronic otitis media with effusion [5] may be caused or exacerbated by GER. Diagnosis of GER with extraesophgeal extension is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the exposure of the upper aerodigestive tract to gastric secretion results in numerous pathologic conditions. Chronic sinusitis, chronic cough, subglottic stenosis, recurrent croup, laryngomalacia, reflex apnea, asthma, recurrent otitis media [4] and also chronic otitis media with effusion [5] may be caused or exacerbated by GER. Diagnosis of GER with extraesophgeal extension is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22][23] Abd El-Fattah et al 20 used dual pH monitoring with the upper pH probe 1 cm above the UES. In a group of 31 children with OME, they diagnosed GER in 6 patients and LPR in 71% of the patients using the cutoff value of pH < 4.0.…”
mentioning
confidence: 99%
“…In a second study, Rozmanic et al 21 applied a dual pH catheter with an upper pH probe in 11 children with OME, and recognized LPR in 3 children and GER in 6 children. Keles et al 22 examined children with OME using a dual pH probe with an upper pH sensor in the proximal esophagus. Other authors have applied a single pH sensor in the distal esophagus.…”
mentioning
confidence: 99%
“…pH probe evidence for GERD is found in up to 56% of children with chronic serous and recurrent otitis media. In children with evidence of pharyngeal and esophageal refl ux on double-probe pH testing, a 10-fold and 5.3-fold greater risk, respectively, of developing middle ear fl uid has been documented compared with children with normal pH studies [25,26].…”
Section: Pathophysiology Of Eord In Otitis Mediamentioning
confidence: 98%